Case series of hand foot mouth disease in children - Thumjaa, A. (International Journal of Contemporary Pediatrics, 2017)
Hand foot mouth disease (HFMD) is a highly contagious disease caused by human enteroviruses. A total of 27 cases of age group 8 months to 10 years, presented with symptoms like skin rash, mouth ulcers, sore throat, fever, cough, abdominal pain and diarrhea. The exanthemas were erythematous maculopapular with few vesicles and enanthems in buccal mucosa, palate and tongue. The treatment of this disease is symptomatic and proper personal hygiene. It is important to establish right diagnosis to avoid epidemics.